Single immunization with an influenza hemagglutinin nanoparticle‐based vaccine elicits durable protective immunity - Shiho Chiba; Tadashi Maemura; Kathryn Loeffler; Steven J. Frey; Chunyang Gu; Asim Biswas; Masato Hatta; Yoshihiro Kawaoka; Ravi S. Kane (Wiley, 2024)
Abstract Vaccination is the most effective strategy to combat influenza. Ideally, potent and persistent vaccine effects would be induced with a single vaccine dose. Here, we designed a virus‐like particle (VLP)‐based vaccine presenting multiple copies of the influenza hemagglutinin (HA) from A/Puerto Rico/8/1934 (PR8HA‐VLP) and examined its immunogenicity and protective efficacy in ferrets. Serum‐neutralizing antibodies were effectively induced against the homologous virus at 3‐week post‐vaccination with a single dose of PR8HA‐VLP with or without adjuvants. When the single‐immunized ferrets were challenged with the homologous virus, virus replication in the nasal mucosa was significantly reduced. Long‐term monitoring of serum titers revealed that after adjuvanted vaccination with PR8HA‐VLP, neutralizing antibodies were retained at similar levels 20‐ to 183‐week post‐vaccination, although a 4‐ to 8‐fold titer decline was observed from 3‐ to 20‐week post‐vaccination. Boost immunization at 183 weeks after the first immunization elicited higher neutralizing antibody titers than those at 3 weeks after the initial immunization in most of the animals. These results confirm that nanoparticle‐based vaccines are a promising approach to effectively elicit durable multiyear neutralizing antibody responses against influenza viruses.